2018
DOI: 10.3390/bs8060053
|View full text |Cite
|
Sign up to set email alerts
|

Violence Exposure and Mental Health of College Students in the United States

Abstract: Background: Despite the well-established link between exposure to violence and mental health problems, less is known about this association among college students. The current study aimed to investigate the association between history of exposure to violence and mental health of American college students. Methods: Healthy Mind Study (HMS, 2016–2017) is a national online survey of 41,898 adult college students. The independent variable was lifetime history of exposure to violence (psychological, physical, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 97 publications
1
8
1
3
Order By: Relevance
“…According to an overview article, chronic arousal due to stress has been identified as a key factor for mental ill-health irrespective of age group [26]. Victimization in young people differs between males and females regarding their perpetrators and places of victimization, but their adverse mental-health associations are similar [45,46,47] and have longstanding consequences for adulthood [48].…”
Section: Introductionmentioning
confidence: 99%
“…According to an overview article, chronic arousal due to stress has been identified as a key factor for mental ill-health irrespective of age group [26]. Victimization in young people differs between males and females regarding their perpetrators and places of victimization, but their adverse mental-health associations are similar [45,46,47] and have longstanding consequences for adulthood [48].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Khrapatina and Berman () found that three fourths of the college students reported at least one adverse childhood experience (75.5%) and approximately one in five reported an ACE score of 4 or more (21.7%). As with other populations, research among college students also reveals childhood trauma to be associated with physical and mental health problems (Assari & Lankarani, ; Karatekin, ; Kim, ; Mortier et al, ; Runtz, ; Singh, Manjula, & Philip, ; You, Chen, Yang, Zhou, & Qin, ; Velikis, Anagnostopoulou, Mastorakou, Triliva, & Gouva, ). These findings have been replicated in different localities and nations outside the United States including China, India, Turkey, and South Korea.…”
Section: Introductionmentioning
confidence: 89%
“…E08: "eu fico mais estressada, ansiosa [...] é mais uma violência psicológica [por ser representante de turma], porque eles me cobram muito de uma coisa que não é minha obrigação eu estou fazendo para ajudar a turma [...]". E14: "Tristeza, [...], às vezes causa ansiedade, angústia, influencia diretamente no emocional..." Deve-se considerar, portanto, que experienciar violência é uma forma de estresse, com características próprias, que corrobora com o comprometimento emocional (Assari & Lankarani, 2018). E11: "Influencia [violência] no comportamento do outro principalmente no que diz respeito a autoestima e o comportamento em questão de concentração nas aulas [...]Muitas influências que houveram, por exemplo, a falta de concentração, não querer vir para a faculdade para não encontrar aquela pessoa ou não querer que aquela atitude [violência] se torne recorrente".…”
Section: Apercepção De Violência Em Sala De Aula E Suas Influências Na Vida Dos Acadêmicosunclassified
“…Outros estudos também referem comprometimento à saúde física e emocional dos discentes, em seu cotidiano universitário. Ansiedade, depressão e comportamento suicida são os três maiores problemas de saúde mental entre universitários que vivenciaram violência (Assari & Lankarani, 2018;Pedrelli et al, 2015). Sentimentos de rebaixamento da auto estima e intenso estresse, também, foram apresentados em estudo com acadêmicos do curso medicina (Peres et al,2014).…”
Section: Apercepção De Violência Em Sala De Aula E Suas Influências Na Vida Dos Acadêmicosunclassified